Victim blaming among young students - V. P. Kurachinskaya; O. A. Kulikova (Вестник университета)
The article presents basic information on the problem of victim blaming, describes the history of the appearance of this concept. Major factors in the formation of victim blaming such as patriarchal attitudes, the phenomenon of a just world, family and upbringing, established social cliches and patterns of relationships and the media have been identified. The results of the study have been presented, from which the level of awareness of young people about the problem of victim blaming and their views in the context of the problem have been outlined. The role of the immediate environment in relation to the victim of the situation has been considered, and the influence of the media on the formation of victim blaming among students has been outlined. The problem outlined reflects the impact of victim blading on young people and the further consequences of this negative experience.